Advances in Metal Matrix Composite Coatings and Layers (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This reprint aims to present modern methods of producing composite materials and composite surface layers and the possibility of controlling properties via the appropriate selection of production parameters. Together, we consider these materials at the macro, micro and nano scale, and assess modern solutions in the field of mechanical engineering and surface engineering. In this reprint, we familiarize ourselves with both the high-energy methods used to modify ferrous materials and the surface properties of non-ferrous materials. It also aims to familiarize the reader with the vast possibilities associated with the production of composite materials. This reprint provides a multidisciplinary forum that focuses on the production, properties and applications of composite materials and composite surface layers. The editors of this Special Issue would like to thank the authors for their invaluable contributions.